ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN MENGGUNAKAN PENDEKATAN INCOME STATEMENT DAN PENDEKATAN SHARIATE VALUE ADDED STATEMENT - Elyanti Rosmanidar (Jurnal Akuntansi & Keuangan Unja, 2015)
A performance assessement of Islamic Banking can be done by analyzing the financial statements. Current financial performance of Islamic Banking refers only Corporate profit are presenter in conventional financial statements. This study amis to examine and obtain empirical evidence about the differences in the financial performance of Islamic Banking with conventional income approach is based on the Entity Theory and Islamic value-added approach is considered more able to represent how the performance of a Business entity because it is based on the Islamic Shariah Enterprise Theory. This Research is quantitative descriptive and comparative study. The data used are secondary data from published financial statements. Analysis is performed using analysis of financial ratios namely ROA, ROE, LBAP, NPM and BOPO. The Population in this study is that Islamic Banking has existed for more than 5 years in Indonesia, has a Branch Office in Jambi and publish their financial statements in the periode of observation (2009-2013). Based on these kriteria, the sampel obtained 3 banks: Bank Mega Syariah, Bank Muamalat Indonesia, Tbk. and Bank Syariah Mandiri Tbk. The analysis technique used in this study is to test the independent sampel t-test. The results showed that Three are significant differences between the financial performance Computer Income statement approach compared to approaches shariate value added statement. Financial performance with SVAS approach has a Bette value than the calculated performance with the IS approach. Keywords: Income Statement, Shariate Value Added Statement, ROA, ROE, LBAP, NPM, BOPO.